Limited Access to Iodized Salt among the Poor and Disadvantaged in North 24 Parganas District of West Bengal, India (Journal of Health, Population and Nutrition, 2010)
Iodine deficiency is endemic in West Bengal as evident from earlier studies. This community-based, crosssectional descriptive study was conducted in North 24 Parganas district during August-November 2005 to assess the consumption of adequately-iodized salt and to ascertain the various factors that influence access to iodized salt. In total, 506 households selected using the multi-stage cluster-sampling technique and all 79 retail shops from where the study households buy salt were surveyed. The iodine content of salt was tested by spot iodine-testing kits. Seventy-three percent of the households consumed salt with adequate iodine content (≥15 ppm). Consumption of adequately-iodized salt was lower among rural residents [prevalence ratio (PR): 0.8, 95% confidence interval (CI) 0.7-0.9], Muslims (PR: 0.8, 95% CI 0.7-0.9), and households with monthly per-capita income of ≤US$ 10 (PR: 0.7, 95% CI 0.6-0.8). Those who heard and were aware of the risk of iodine-deficiency disorders and of the benefit of iodized salt were more likely to use appropriate salt (PR: 1.2, 95% CI 1.1-1.3). Those who were aware of the ban on non-iodized salt were more likely to consume adequately-iodized salt (PR: 1.1, 95% CI 1.01-1.3). The iodine content was higher in salt sold in sealed packets (PR: 2.9, 95% CI 1.8-4.8) and stored on shelves (PR: 1.6, 95% CI 1.3-2.0). Seventy-two percent of the salt samples from the retail shops had the iodine content of ≥15 ppm. The findings indicate that elimination of iodine deficiency will require targeting the vulnerable and poor population. Key words: Community-based studies; Cross-sectional studies; Descriptive studies; Goitre; Iodine; Iodine deficiency; Iodized salt; Socioeconomic factors; India DOI: 10.3329/jhpn.v28i4.6043 J HEALTH POPUL NUTR 2010 Aug;28(4):369-374